Morphological and flexural properties of lightweight gypsum based fiber reinforced composite - Jorillo, Pablo A. (Philippine Engineering Journal)
This paper describes the results of the experimental investigations of the properties of lightweight gypsum based fiber reinforced composites. Two general types of fiber reinforcement were examined, namely, polymer-based fibers and natural fibers. The study is essentially a developmental research with the objective of evaluating the properties of natural fibers in comparison with synthetic fibers of the same density in a gypsum matrix. A gypsum cellulose pulp and a gympsum Shirasu balloon sand were used as lightweight gypsum matrices. Experimental and analytical results on both standard specimens and full-scale structural elements such as wall panel are presented.